Status Penyakit Periodontal pada Pria Perokok Dewasa - Rohmawati, Nia; Santik, Yunita Dyah Puspita (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2019)
The prevalence of periodontal disease in Klaten Regency incresed in 2017 from 2016. Jogonalan I Public Health Center has the second highest prevalence of periodontal disease cases, the number. The purpose of this study was to determine what risk factors were associated with periodontal disease status in adult male smokers. This type of research is observational analytic with aapproach case control. The sample set was 42 cases and 42 control samples with purposive sampling technique. The results showed that smoking status (p = 0.017), length of smoking (p = 0.037), number of cigarettes (p = 0.040), brushing behavior (p = 0.030), consumption of fruit and vegetables (p = 0.008) were associated with periodontal disease status in adult male smokers. The conclusion of this study is that there is a relationship between smoking status, length of smoking, number of cigarettes, tooth brushing behavior and consumption of vegetable fruit with periodontal disease status, and there is no relationship between types of cigarettes and coffee consumption with periodontal disease status. Keywords: Risk Factors, Periodontal, Smokers, Adults